Brazilian community health agents and qualitative primary healthcare information - Zanchetta, Margareth Santos; Pinto, Rogério Pinto; Garcia, Wilson Galhego [UNESP]; Cunha, Zeilma da; Cordeiro, Hésio de Alburquerque; Fagundes Filho, Francisco E.; Pinho, Mônica A. l.; Voet, Susan M. V.; Talbot, Yves; Caldas, Rodrigo S.; Souza, Thiago J. de [UNESP]; Costa, Edwaldo [UNESP] (Cambridge University Press (CUP), 2014)
The aim of this study was to explore female community health agents’ views about the value of recording qualitative information on contextual health issues they observe during home visits, data that are not officially required to be documented for the Brazilian System of Primary Healthcare Information. Background: The study was conducted in community primary healthcare centres located in the cities of Araçatuba and Coroados (state of São Paulo) and Rio de Janeiro (state of Rio de Janeiro), Brazil. Methods: The design was a qualitative, exploratory study. The purposeful sampling criteria were being female, with a minimum of three years of continuous service in the same location. Data collection with 62 participants was conducted via 11 focus groups (in 2007 and 2008). Audio files were transcribed and submitted to the method of thematic analysis. Four themes guided the analysis: working with qualitative information and undocumented observation; reflecting on qualitative information; integrating/analysing quantitative and qualitative information; and information-sharing with agents and family health teams. In 2010, 25 community health agents verified the final interpretation of the findings. Findings: Participants valued the recording of qualitative, contextual information to expand understanding of primary healthcare issues and as an indicator of clients’ improved health behaviour and health literacy. While participants initiated the recording of additional health information, they generally did not inform the family health team about these findings. They perceived that team members devalued this type of information by considering it a reflection of the clientele’s social conditions or problems beyond the scope of medical concerns. Documentation of qualitative evidence can account for the effectiveness of health education in two ways: by improving preventative care, and by amplifying the voices of underprivileged clients who live in poverty to ensure the most appropriate and best quality primary healthcare for them.
Keywords: Brazil; Community health agents; Deprived communities; Information system; Primary healthcare; Qualitative health information; Rio de Janeiro; São Paulo